The State of the Teutonic Order as a Socialist Society - Brzechczyn, Krzysztof (Rodopi, 1993)
This paper aims to analyze the social structure of the society in Teutonic state (1226-1525), which was distinct from structure of estate societies. The author put hypothesis that Teutonic Knight monopolised in their state political, economical and spiritual power. In the light of this thesis certain trends from history of the state of Teutonic Order are explained.
Keywords: Order of Teutonic Knights; Socialism; Non-Marxian historical materialism; Estate society